I wonder why the sea is salty : and other questions about the oceans - Ganeri, Anita (Danbury, Connecticut : Grolier Inc, 1999)
With information and quirky facts to explain everything from 'Which sea animals sing like canaries?' to 'What is sand made of?'.
Includes index
Keywords: Salty